Preparation of Vertically Aligned ZnO/TiO2 Core-Shell Composites for Dye-Sensitized Solar Cells - Lung-Chuan Chen; Shuei-Feng Tsai; Jean-Hong Chen; Gaun-Wen Wang (International Journal of Photoenergy)
Vertically aligned ZnO/TiO2 (VA-ZnO/TiO2) core-shell composites deposited on ZnO-seeded indium tin oxide (ITO) glasses have been synthesized by a chemical bath deposition approach for growing one-dimensional ZnO structure followed by a spin procedure for coating TiO2 on the surface of ZnO structure. The influences of the cycles of spin coating of TiO2 (CSCT) on the properties of VA-ZnO/TiO2 and performances of the assembled DSSCs were studied. The power conversion efficiency of the VA-ZnO/TiO2-based DSSC measured under illumination of 100 mW/cm2 and AM 1.5 can reach 0.81%, representing 93% improvement when compared with that of the pristine VA-ZnO electrode (0.42%). The intensity-modulated photocurrent spectroscopy (IMPS) and electrochemical impedance spectroscopy (EIS) were applied to study the kinetics and interfacial transfer of the photogenerated electrons. Both the photocurrent and power conversion efficiency correlate well with the steady state electron density. Enlargement in surface area and dye adsorption, suppression of dissolution of Zn2+, diminishment in electron recombination, and fast transfer of injected electrons from excited dyes to TiO2 conduction bands arising from coating TiO2 on VA-ZnO are regarded as the predominant causes for this improvement.